2020
DOI: 10.3390/v12101100
|View full text |Cite
|
Sign up to set email alerts
|

Features of Nuclear Export Signals of NS2 Protein of Influenza D Virus

Abstract: Emerging influenza D viruses (IDVs), the newest member in the genus Orthomyxovirus family, which can infect and transmit in multiple mammalian species as its relatives the influenza A viruses (IAVs). Additional studies of biological characteristics of IDVs are needed; here, we studied the characteristics of IDV nonstructural protein 2 (NS2), which shares the lowest homology to known influenza proteins. First, we generated reassortant viruses via reverse genetics to analyze the segment compatibility and gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Rescue experiments with NS2-deletion mutants suggested that the NOR of NS2 contains no functional domain responsible for viral infectivity, and deletion mutants with other regions in the C-terminal region could not be generated. A recent report indicated that IDV NS2 includes three nuclear export signals (NESs) at positions 66-75, 97-107, and 136-146, which may mediate the chromosome region maintenance 1 (CRM1)-dependent nuclear export pathway, similar to IAV NS2 [30]. Our rescue experiments suggest that NS2∆NOR, which retains these NESs, might play an equivalent role to intact NS2 in viral infectivity.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Rescue experiments with NS2-deletion mutants suggested that the NOR of NS2 contains no functional domain responsible for viral infectivity, and deletion mutants with other regions in the C-terminal region could not be generated. A recent report indicated that IDV NS2 includes three nuclear export signals (NESs) at positions 66-75, 97-107, and 136-146, which may mediate the chromosome region maintenance 1 (CRM1)-dependent nuclear export pathway, similar to IAV NS2 [30]. Our rescue experiments suggest that NS2∆NOR, which retains these NESs, might play an equivalent role to intact NS2 in viral infectivity.…”
Section: Discussionmentioning
confidence: 54%
“…The NS1 and NS2 proteins possess an overlapping identical 63-amino-acid sequence at each N-terminal region and subsequent unique sequences in the downstream region of each protein, which are translated by different reading frames, even in the Cterminal overlapped gene region (Figure 1A). According to recent reports, the IDV NS1 protein antagonizes cellular type I interferon response [29] and the NS2 protein is a nuclear export protein (NEP) that mediates the nuclear export of viral RNPs [30], similar to NS proteins of the other type viruses. However, the biological functions of these proteins have not been fully elucidated at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…After staining with secondary antibodies, cells were stained with 4,6-diamidino-2-phenylindole (DAPI) for 10 min. Finally, images were acquired using a confocal microscope (Nikon, Japan) equipped with a Plan Apo objective (60×/1.40, oil immersion; Nikon, Japan) and CFI eyepiece (10×/22; Nikon) ( 58 ).…”
Section: Methodsmentioning
confidence: 99%
“…This limited protection as well as the presence of diverse genetic variants in co-circulation caused re-infection, and thereby a high prevalence of IDV in cattle [147]. In the case of IDV, the third (136-146 aa) nuclear export signal (NES) of IDV NS2 among the three separate NES regions is majorly responsible for the nucleocytoplasmic transport through the chromosome region maintenance 1/Xpo1 (CRM1) pathway [262]. With the increased clinical cases of ICV-related pneumonia in children along with the absence of antiviral immunity specific to ICV, more and more studies are needed in this area.…”
Section: Antiviral Innate Immunity To Icv and Idvmentioning
confidence: 99%